(3x - y)(x + 7y)
(3x + y)(2x - 7y)
(3x + y)(x - 7y)
(3x - y)(2x + 7y)
Correct answer is A
(2x + 3y)2 - (x - 4y)2
= (2x + 3y)(2x + 3y) - (x - 4y)(x - 4y)
= 4x2 + 12xy + 9y2 - (x2 - 8xy+ 16y2)
= 4x2 + 12xy + 19y2 - x2 + 8xy - 16y2
= 3x2 + 20xy - 7y2
= 3x2 + 21xy - xy - 7y2
= 3x(x + 7y) - y(x + 7y)
= (3x - y)(x + 7y)
If y = x Sin x, find dydx when x = π2...
In the diagram O is the center of the circle, ∠SOR = 64° and ∠PSO = 36°. C...
A fair die is rolled once. What is the probability of obtaining a number less than 3? ...
The distance between the point (4, 3) and the intersection of y = 2x + 4 and y = 7 - x is ...